Once Upon a Time in the Twenty-First Century : Unexpected Exercises in Creative Writing - Behn, Robin (Book collections on Project MUSE., 2021)
""Once upon a Time in the Twenty-First Century" is an innovative, inspirational, and unique creative writing textbook/handbook that fills many educational needs and gaps. Designed to appeal to a wide range of readers and writers - from teenagers to young adults, from grade nine through college and beyond - this volume of exercises is of inestimable value to students and teachers in the traditional classroom, a growing number of homeschoolers, others who are served by "distance learning," those who are part of a writing club or group, and independent writers and learners of all ages. The book is based on years of hands-on experiences in the teaching of creative writing in public high schools and after-school writing clubs. The book begins with poet Robin Behn's introduction and is followed by three writing sections: Genres and Forms; Sources and Methods; and Style and Subject. In each section, Behn offers a brief introduction to how to get started and specific ways to develop one's writing, and each introduction is then followed by extensive exercises that draw on classic literature and popular culture, ranging from Flannery O'Connor and Tennessee Williams to Elizabeth Bishop and Gertrude Stein, from Thomas Wolf and Pablo Neruda to Salman Rushdie and Arlo Guthrie. As part of Behn's layered approach to learning, she integrates within the exercises apt examples of student writings that have emerged from actual use of the exercises in both the classroom and in writing groups. The book concludes with general advice and direction on how to get published"--